Can Shear Wave Elastography be of Value in the Assessment of Cervical Strength for the Prediction of Preterm Birth? - O'Hara, Sandra Joyce (Curtin University, 2020)
Preterm birth has long term health consequences. If the cervix softens early in pregnancy then the likelihood of preterm birth occurring is high. Shear wave elastography is a new development of ultrasound technology that can assess the stiffness of tissues. This research developed a shear wave elastography technique for use on the cervix to assess if it can predict cervical insufficiency with greater sensitivity than the current standard of cervical length measurement.